Topology Control and Opportunistic Routing for Underwater Acoustic Sensor Networks - Coutinho, Rodolfo W. L.; Boukerche, Azzedine; Vieira, Luiz; Loureiro, Antonio A. F. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2018)
Underwater wireless sensor networks (UWSNs) are emerging to enable large-scale ocean monitoring with the goal of reducing the human knowledge gap of underwater environments and the life underneath them. However, several challenges still limit the deployments of UWSNs to small-scale and confined underwater monitoring applications. The goals of this thesis is to investigate and develop analytical models, algorithms and protocols in order to tackle the fundamental data communication challenge in the underwater environment, and advance the state-of-the-art towards feasible large-scale deployment of UWSN applications.